(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This annotation explores innovative pedagogical approaches for teaching pharmaceutical terminology in English. The article delves into methods that go beyond traditional instructional techniques, emphasizing dynamic and engaging strategies. Immersive case studies, multimedia presentations, online modules, and gamified learning platforms are discussed as methods to enhance student comprehension and application of pharmaceutical terms in authentic contexts. The annotation underscores the importance of practical application through role-playing exercises and collaborative projects, promoting active engagement and communication skills development.